Circle of the 9 muses : a storytelling field guide for innovators and meaning makers - Hutchens, David, 1967- (Hoboken, New Jersey : Wiley, 2015)
This book offers any leader a guide for finding, telling, and drawing value from their organization's unique stories. With this practical guide, storytelling can become a powerful managerial asset in your management toolbox. Hutchens reveals which stories are the right ones to tell and clearly shows how stories can bring employees, customers, and other partners together. Filled with illustrative examples and helpful templates, this innovative road map explains how stories can connect with your company's most urgent initiatives such as change management, knowledge management, culture and identity, engagement, branding, innovation, attracting talent, articulating vision and purpose, generating marketplace support, and more. --
Part I. Fundamentals -- Part II. Branching out.
Includes index.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Communication in management; Communication in organizations; Creative ability in business; Corporate culture; Storytelling; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Communication in management; Communication in organizations; Corporate culture; Creative ability in business; Storytelling; Electronic books; Electronic books